2002
DOI: 10.1074/jbc.m201901200
|View full text |Cite
|
Sign up to set email alerts
|

Smurf1 Regulates the Inhibitory Activity of Smad7 by Targeting Smad7 to the Plasma Membrane

Abstract: Smad ubiquitin regulatory factor 1 (Smurf1), a HECTtype E3 ubiquitin ligase, interacts with inhibitory Smad7 and induces cytoplasmic localization of Smad7. Smurf1 then associates with transforming growth factor-␤ type I receptor (T␤R-I) and enhances the turnover of this receptor. However, the mechanisms of the nuclear export and plasma membrane localization of the Smurf1⅐Smad7 complex have not been elucidated. We show here that Smurf1 targets Smad7 to the plasma membrane through its N-terminal conserved 2 (C2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 37 publications
10
124
1
4
Order By: Relevance
“…In ATLL cells, Smad7 predominantly localizes to the nucleus and binds to the promoter region of TGF-b1 responsive genes with SRE to inhibit formation of the R-Smad/DNA complex. The differential localization of Smad7 between cell types is currently unknown; however, Smurf-mediated nuclear export of Smad7 has been shown in several studies (Kavsak et al, 2000;Suzuki et al, 2002). In our study using DNA microarrays, we found that the expression level of Smurf1 in acute-type ATLL cells was higher than in CD4 þ T lymphocytes from normal volunteers; however, the expression of Smurf2 was lower in ATLL cells (data not shown).…”
Section: Discussionmentioning
confidence: 45%
“…In ATLL cells, Smad7 predominantly localizes to the nucleus and binds to the promoter region of TGF-b1 responsive genes with SRE to inhibit formation of the R-Smad/DNA complex. The differential localization of Smad7 between cell types is currently unknown; however, Smurf-mediated nuclear export of Smad7 has been shown in several studies (Kavsak et al, 2000;Suzuki et al, 2002). In our study using DNA microarrays, we found that the expression level of Smurf1 in acute-type ATLL cells was higher than in CD4 þ T lymphocytes from normal volunteers; however, the expression of Smurf2 was lower in ATLL cells (data not shown).…”
Section: Discussionmentioning
confidence: 45%
“…Mutations of the PY motif of Smads 1 and 5 proteins prevent them to interact with Smurf1 and inhibit the degradation of these Smad proteins (Zhu et al, 1999). Smurf1 is located in the nucleus and it is exported to the cell membrane and cytoplasm when it binds Smad6 or 7 and induces the degradation of type I TGFβ and BMP receptors and Smads 1 and 5 (Ebisawa et al, 2001;Suzuki et al, 2002;Murakami et al, 2003). Several lines of evidence suggest that Smurf1 may have synergistic effect with Smad6 and inhibit BMP signaling (Murakami et al, 2003;Horiki et al, 2004).…”
Section: Ubiquitin-proteasome Degradation Of Bmp Signaling Proteinsmentioning
confidence: 99%
“…The original constructions of constitutively active forms of TGF-β type I and BMP type IB receptors [TβR-I(TD) and BMPR-IB-(QD) respectively], Smad1, Smad2, Smad3, Smad4, Smad5, Smad8 and NEDD4 were described previously [19,32]. The open reading frame of NEDD4-2 was generated by a PCRbased approach from a cDNA clone of KIAA0439 (Kazusa DNA Research Institute, Chiba, Japan) as a template, and subcloned into EcoRI/XhoI-digested FLAG-pcDNA3 [32].…”
Section: Dna Construction and Transfectionmentioning
confidence: 99%
“…In addition, Smurfs 1 and 2 interact with nuclear Smad7 and induce translocation of Smad7 to the cytoplasm in a CRM-1 (chromosome region maintenance 1)-dependent fashion [16][17][18]. The Smurf1-Smad7 complex is then targeted to the cell membrane through the N-terminal C2 domain in Smurf1, and associates with TβR-I (TGF-β type I receptor) [19]. After binding to TβR-I, Smurfs 1 and 2 induce ubiquitin-mediated degradation of TβR-I.…”
Section: Introductionmentioning
confidence: 99%